Flexural behavior of reinforced concrete beams using waste marble powder towards application of sustainable concrete - Karalar, Memduh; Özkılıç, Yasin Onuralp; Aksoylu, Ceyhun; Sabri Sabri, Mohanad Muayad; Beskopylny, Alexey N.; Stel’makh, Sergey A.; Shcherban’, Evgenii M. (Frontiers in Materials, 2022)
The performance of waste marble powder as partial replacement of cement is examined to achive more sustainable concrete. Pursuant to this goal, a total of 15 specimens were manufactured and then tested to examine the bending behavior. The effects of longitudinal reinforcement ratio and waste marble powder ratio were selected as variables. The experimental results showed that different proportions of tension reinforcement and waste marble powder had a different crack and bending impacts on reinforced concrete beams. As the waste marble powder amount in the concrete mixture is increased from 0% to 40%, it is detected that the crack type changes as a shear crack from the flexural crack as the amounts of waste marble powder increase the mixing ratio. The experimental findings revealed that the waste marble powder can be successfully used as 10% of partial replacement of cement. Increasing waste marble powder ratio more than 10% can significantly decrease the capacity of the beams, espically when longitudiunal reinforcement ratio is high. The influence of waste marble as partial replacement on the capacity decreases as the longituidunal reinforcement ratio decreases. Therefore, 10-20% marble waste can be utilized as replacement of cement when the longitudinal reinforcement ratio is close to balanced ratio and more than 20% waste marble was ratio should be avoided for any cases.